The Effects of Natural Pushing Together with a Preliminary Controlled Breathing of Yoga on Duration of the Second Stage of Labor and Postpartum Fatigue in Primiparous Women - สุขยิ่ง, วันณภา; พุมดวง, ศศิธร; ธิติมาพงษ์, เบญญาภา (Princess of Naradhiwas University Journal, 2018)
The purposes of this quasi-experimental research were to examine the effects of natural pushing together with a preliminary controlled breathing of Yoga on the duration of the second stage of labor and postpartum fatigue of primiparous women. The sample comprised pregnant women at an antenatal clinic who were admitted later at the Labor Unit at Mayo Hospital in Pattani Province. Sixty-six primiparous women with normal pregnancy were randomized to either a control group and experimental group. There were 33 women in each group. Women in the experimental group did natural pushing during uterine contraction and did preliminary controlled breathing during relaxation period (no uterine contraction) while the control group received standard care provided by the nurses. Instruction on preliminary controlled breathing of Yoga included teaching plan, video, and brochures. The data collection instruments were demographic questionnaire, labor data record, and postpartum fatigue after 2 hour questionnaire. The postpartum fatigue after 2 hour questionnaire was tested yielding Cronbach’s alpha of .90. Data were analyzed using frequency, percentage, mean, standard deviation and t-test and Mann-Whitney U test. The results of this study revealed that after the experimental, the experimental group had significantly shorter mean rank of duration of second stage of labor than those in the control group (Z = -3.98, p < .001) and had significantly less mean of 2 hour postpartum fatigue than those of the control group (M = 18.21, S.D. = 10.26 vs M = 32.36, S.D. = 11.68, p < .001). In conclusion, natural pushing technique together with a preliminary controlled breathing of Yoga decreased pushing time and 2hour postpartum fatigue. It should be promoted to use with women during the second stage of labor.